Geographical information system-based forest fire risk assessment integrating national forest inventory data and analysis of its spatiotemporal variability. (June 2017) - You, Weibin; Lin, Li; Wu, Liyun; Ji, Zhirong; Yu, Jian'an; Zhu, Jianqin; Fan, Yunjian; He, Dongjin
Highlights: A conceptual frame for fire risk mapping was developed integrating the National Forest Resource Inventory Database. A potential forest fire risk and map risk zones in a China's heritage site were assessed using GIS. The spatio-temporal variation of forest fire risk was examined by spatial analysis method. Abstract: Improvements in forest fire risk estimation and mapping fire risk zones are vital to reduce the negative impacts of fire and to facilitate planning for the protection of forested areas. This is especially important for places with little previous data on fire history. This paper presents an improved conceptual scheme for the assessment and mapping of fire risk using a Forest Resource Inventory Database, based on four aspects of topographical, human activity, climate, and forest characteristics factors. We selected 12 variables based on our defined conceptual scheme to generate a synthetic forest fire risk index (FRI) to quantify potential forest fire risk and map risk zones in the Wuyishan Scenery District (WSD), a world heritage site that located in the northwest of Fujian province, People's Republic of China. Spatial statistics were used to examine the spatio-temporal variation of FRI. The results showed the main fire risk zones in the WSD were in the low or moderate categories (accounting for 76.7% of the total area of the WSD in 1997 and 79.2% in 2009). The spatial heterogeneity of FRI showed anisotropic variability characteristics which changed over time. From 1997 to 2009, there was an increasing influence from both autocorrelation factors and random factors. Moreover, these factors played almost equally important roles in forest fire processes in the WSD. The fire risk map was applied to assess the vulnerability of cultural heritage resources in the WSD. Most were located in low- or moderate-risk areas, and therefore would be at low risk from potential fire damage.